Spatial and Temporal Assessment of Flood Affected Areas in Dhubri District of Assam Using RS&GIS - Choudhury, Mrinal; Moshahary, Jwngsar; Basumatary, Banjaigra Z.; Deka, Pompy; Sarma, Bhaskarjyoti; Ahmed, Perves (International Journal of Bio-resource and Stress Management, 2025)
The experiment was conducted during September to December 2024 at SCS College of Agriculture, AAU, Dhubri, Assam, India using secondary data collected from Sentinel-1A satellite 10-meter spatial resolution for study year 2019–2024. The objective of the study was to assess the spatial and temporal variability of flood inundation and submergence of agricultural land in the district using Remote Sensing (RS) and Geographic Information Systems (GIS). The flood incidents at block levels in the entire Dhubri district over the period of 2020 to 2024 were considered for the study. For this purpose, Sentinel-1 SAR imagery of the study area and the period were extracted using Google Earth Engine. Significant spatial and temporal variations in flood inundations were observed during the years from 2020 to 2024 in all the blocks under the Dhubri district. Birsing Jarua block emerged as the most vulnerable one, with flooded areas increasing from 19.24% in 2022 to 49.12% in 2024, leading to a two and half times rise in cropland inundation. Nayeralga, Mahamaya, and Chapor-Salkocha blocks also showed high vulnerability towards intensified flooding. Conversely, Rupshi, Bilasipara, and Golaganj blocks exhibited declining flood extents over the period of study. The study highlighted the need for block level integrated contingency plan in high-risk zones to mitigate future agricultural damage caused by flood in the district.